Induced breeding and management practices for mass seed production of nutrition-sensitive punti fish - Ali, Hazrat; Dubey, Sourabh; Biswas, Ashutosh; Jaman, Ahmed; Rashid, Harun (WorldFish, 2024)
The practical guideline ‘Induced Breeding and Management Practices for Mass Seed Production of Nutrition-Sensitive Punti Fish’ has been developed under the CGIAR Initiative on Asian Mega-Deltas. The swamp barb (Puntius chola) and pool barb (Puntius sophore), collectively referred to as "punti" in the Ganges Delta, are widely distributed across South Asia. This user-friendly manual provides a step-by-step protocol for the induced breeding of punti, addressing the absence of standardized techniques that previously hindered its broader adoption. It also offers essential guidance on seed nursery management, packaging, and transportation systems, ensuring successful seed production and distribution. The nine-step process supports easy implementation by fish hatcheries, promoting the scaling of nutrition-sensitive aquaculture and enhancing food security in regions where punti is of nutritional significance.